Teleeducation and Telepathology for Open and Distance Education - Janusz Szymas (Analytical Cellular Pathology)
Our experience in creating and using telepathology system and multimedia database for education is described. This program packet currently works in the Department of Pathology of University Medical School in Poznan. It is used for self‐education, tests, services and for the examinations in pathology, i.e., for dental students and for medical students in terms of self‐education and individual examination services. The system is implemented on microcomputers compatible with IBM PC and works in the network system Netware 5.1. Some modules are available through the Internet. The program packet described here accomplishes the TELEMIC system for telepathology, ASSISTANT, which is the administrator for the databases, and EXAMINATOR, which is the executive program. The realization of multi‐user module allows students to work on several working areas, on random be chosen different sets of problems contemporary. The possibility to work in the exercise mode will image files and questions is an attractive way for self‐education. The standard format of the notation files enables to elaborate the results by commercial statistic packets in order to estimate the scale of answers and to find correlation between the obtained results. The method of multi‐criterion grading excludes unlimited mutual compensation of the criteria, differentiates the importance of particular courses and introduces the quality criteria. The packet is part of the integrated management information system of the department of pathology. Applications for other telepathological systems are presented.